Parental Divorce: Impact on Socio-Psychological Behavior and Academic Performance of Students in Teacher's Perception. Issue 6 (18th August 2021) - Iqbal, Mussarat; Khalid, Muhammad Saifullah; Rehman, Nadia; Yanping, Li
ABSTRACT: Divorce situates severe consequences on the family environment, annually significant numbers of children face such life transitions. The purpose of this study was to explore the relationship of parental divorce with social, psychological behaviors and academic performance of separated family children in the perception of elementary teachers. This study surveyed socio-psychological behavior and academic performance indicators. Sixty teachers participated in the study; they were currently teaching such children. The statistical measures of study constitute a significant negative impact on children's social and academic performance. This study concluded the distressing effect of divorce on elementary students.